Association between event-free survival and overall survival in early-stage triple-negative breast cancer - Huang, Min; Fasching, Peter; Haiderali, Amin; Xue, Weiguang; Pan, Wilbur; Karantza, Vassiliki; Yang, Fan; Truscott, James; Xin, Yiqiao; O'Shaughnessy, Joyce (Future Oncology, 2024)
Aim: This study evaluated event-free survival (EFS) as a surrogate outcome for overall survival (OS) in neoadjuvant therapy for early-stage triple-negative breast cancer (eTNBC). Methods: Meta-regression analyses based on a targeted literature review were used to evaluate the individual- and trial-level associations between EFS and OS. Results: In the individual-level analyses, 3-year EFS was a significant predictor of 5-year OS (p < 0.01; coefficient of determinations [R2]: 0.82 [95% CI: 0.68-0.91]). Additionally, there was a statistically significant association between the treatment effect on EFS and OS at the trial level (p < 0.001; R2: 0.64 [95% CI: 0.45-0.82]). Conclusion: This study demonstrates significant associations between EFS and OS and suggests that EFS is a valid surrogate for OS following neoadjuvant therapy for eTNBC.
EVALuna2:547163